Ammonia borane alcoholysis hydrogen production catalyst of NiO-CuO / Fe3O4 with three-phase interface as well as preparation method and application of ammonia borane alcoholysis hydrogen production catalyst

The preparation of NiO-CuO/Fe3O4 catalyst with three-phase interface by solvent thermal synthesis method, solving the problems of insufficient activity and high cost of existing catalysts, achieving high-efficiency hydrogen production reaction of ammonia boranyl alcoholylation, and achieving magnetic recovery under external magnetic field , which has enhanced the industrial application potential of catalysts.

CN119114082APending Publication Date: 2024-12-13HUIZHOU HEALTH VOCATIONAL & TECH COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411093788.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing catalysts are insufficient in hydrogen production reaction of ammonia boranolyl, high cost and difficult to recover, limiting the industrial application of hydrogen energy technology.

Method used

The NiO-CuO/Fe3O4 catalyst with three-phase interface was prepared by solvent-thermal synthesis method. NiO and CuO were uniformly deposited onto the Fe3O4 microspheres through impregnation-calcination method to form a heterostructure, optimize the electronic structure and regulate the nickel-copper ratio. Achieve magnetic recycling.

Benefits of technology

The catalytic activity and cyclic performance of the catalyst are improved, and the TOF value reaches 13.5molhydrogen min-1molNi+Cu-1 is low-cost, easy to industrially produce, and magnetic recovery is achieved under the external magnetic field, which significantly enhances the industrial application potential of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114082A_ABST
    Figure CN119114082A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an ammonia borane alcoholysis hydrogen production catalyst of NiO-CuO / Fe3O4 with a three-phase interface, Fe3O4 microspheres are synthesized by adopting a solvothermal synthesis method, then NiO and CuO are deposited on the surfaces of the Fe3O4 microspheres by adopting a dipping-calcining method, an obtained sample is a heterostructure with the three-phase interface, the three-phase interface is NiO-CuO, CuO-Fe3O4 and NiO-Fe3O4, and the three-phase interface is one of NiO-CuO, CuO-Fe3O4 and NiO-Fe3O4. The electronic structure of the catalyst can be optimized by charge transfer among three-phase interfaces, so that the catalytic performance of the catalyst is improved. In addition, the nickel-copper ratio can be regulated and controlled in the synthesis process to further optimize the components of the catalyst; the whole preparation process is simple to operate, environment-friendly, good in experimental reproducibility, low in cost and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalyst synthesis, and in particular to a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst with a three-phase interface, and a preparation method and application thereof. Background Art

[0002] Ammonia borane NH3BH3 (AB) is a unique molecular complex. It has become one of the most promising chemical hydrogen storage materials because of its high (19.6wt%) hydrogen storage capacity and relatively low hydrogen release temperature (less than 350℃). Therefore, the research on NH3BH3 hydrogen storage materials is of great significance for the development of hydrogen energy. However, the hydrogen release rate of ammonia borane in methanol is extremely slow. Therefore, the development of catalysts that accelerate its alcoholysis to produce hydrogen has always been the focus of research in this field. Catalysts play a very important role in the alcoholysis of ammonia borane to produce hydrogen. At present, there are many catalysts that can be used in the alcoholysis of ammonia borane, including Pd-based, Pt-based, Ru-based catalysts, etc. Studies have shown that catalysts can not only greatly increase the reaction rate, but also increase the yield and selectivity of hydrogen. However, most of the precious metal catalysts are currently expensive and cannot be recovered after use, so they cannot be used on a large scale. Therefore, it is urgent to develop a catalyst with high activity, controllable cost and easy recycling. At the same time, some non-precious metal catalysts such as nickel, copper and other metals or alloys have a certain catalytic effect in the production of hydrogen by alcoholysis of ammonia borane. But overall, their activity still needs to be improved to meet the needs of rapid industrial hydrogen production. The electronic structure of nanostructured catalysts has an important influence on their activity. By rationally designing heterogeneous catalysts and regulating the direction and amount of charge transfer between phase interfaces to optimize their electronic structure, it is expected to obtain catalytic materials with higher activity. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst with a three-phase interface. The preparation method of the present invention is simple to operate, environmentally friendly, has good experimental reproducibility, low cost, and is easy for industrial production. The prepared catalyst can achieve magnetic recovery under an external magnetic field.

[0004] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for preparing ammonia borane alcoholysis hydrogen production catalyst having a NiO-CuO / Fe3O4 three-phase interface, comprising the following steps:

[0005] (1) Take a certain amount of soluble divalent iron salt and dissolve it in 40 ml of ethylene glycol to form solution A;

[0006] (2) Dissolve 0.2 mol of sodium hydroxide in 8 ml of water, then add 30 ml of ethylene glycol and stir to obtain solution B;

[0007] (3) Mixing solution A and solution B, stirring evenly, transferring them into a reaction kettle and reacting them at 130° C. for 6 hours, filtering and cleaning, collecting the solid powder sample and placing it in a vacuum oven to dry for a period of time;

[0008] (4) Weigh a certain amount of Fe3O4 powder synthesized in step (3), place it in a mixed aqueous solution containing a certain amount of copper acetate and nickel acetate, stir for 20 minutes, and then place it in an oven at 60-95°C to dry for 2-3 hours;

[0009] (5) After drying into a paste, the paste was transferred to a tube furnace and calcined at 450° C. for 3 hours in a nitrogen atmosphere.

[0010] Preferably, the soluble divalent iron salt in step (1) is FeSO4·7H2O.

[0011] Preferably, in step (4), 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate are dissolved in 10 ml of aqueous solution.

[0012] Preferably, the stirring time in step (3) is 1 hour.

[0013] Preferably, in step (4), after stirring for 20 minutes, the mixture is placed in an oven and dried at 80° C. for 3 hours.

[0014] Preferably, in step (1), 3 mmol of FeSO4·7H2O is dissolved in 40 ml of ethylene glycol to form solution A.

[0015] Preferably, in step (3), the solid powder sample is dried in a vacuum oven at 60° C. for 4 hours.

[0016] Another object of the present invention is to provide a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst with a three-phase interface, which is prepared by the above-mentioned preparation method.

[0017] The ammonia borane alcoholysis hydrogen production catalyst prepared by the above method is used in catalyzing the alcoholysis of ammonia borane to produce hydrogen.

[0018] The solution of the present invention has the following beneficial effects:

[0019] (1) The present invention adopts a solvent thermal synthesis method to synthesize Fe3O4 microspheres, and then uses an impregnation-calcination method to uniformly deposit NiO and CuO on the surface of the Fe3O4 microspheres. The obtained sample is a heterogeneous structure with three-phase interfaces. The three phase interfaces are NiO-CuO, CuO-Fe3O4, and NiO-Fe3O4. The charge transfer between the three-phase interfaces can optimize the electronic structure of the catalyst and thus improve its catalytic performance. In addition, the nickel-copper ratio can be adjusted during the synthesis process to further optimize the components of the catalyst. The entire preparation process is simple to operate, environmentally friendly, has very good experimental reproducibility, and is low in cost and easy to industrialize.

[0020] (2) The obtained sample has weak ferromagnetism (such as Figure 5 As shown), the synthesized catalytic material can be magnetically recovered under external magnetic field conditions (such as Figure 6 In addition, the catalyst was tested for catalytic cycle performance using a magnetic recovery method, and it was found that the catalyst had high cycle performance and stability, with almost no significant activity loss after 6 cycles (as shown in Figure 2). Figure 8 shown).

[0021] (3) The NiO-CuO / Fe3O4 ternary oxide prepared by the present invention exhibits excellent performance in catalyzing the alcoholysis of ammonia borane to produce hydrogen, especially when the nickel and copper feed ratio is 1:1, the catalytic activity is the highest, and the TOF value is as high as 13.5 mol hydrogen min -1 mol Ni+Cu -1 Given its low cost, it is expected to achieve industrial preparation of catalysts for catalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a TEM photo of the sample obtained in Example 4 of the present invention;

[0023] Figure 2 HRTEM photo of the sample obtained in Example 4;

[0024] Figure 3 Element line scanning analysis of the sample obtained in Example 4;

[0025] Figure 4 XRD spectra of samples obtained in Examples 1 and 4;

[0026] Figure 5 Room temperature hysteresis loop of the sample obtained in Example 4;

[0027] Figure 6 for Figure 5 A partial enlarged view of

[0028] Figure 7The photos of the catalyst of Example 4 that was magnetically recovered under an external magnetic field are shown below: (a) the catalyst dispersed in the reaction solution, (b) the catalyst under an external magnetic field, and (c) the catalyst redispersed in the solution by ultrasonic vibration.

[0029] Figure 8 This is a cyclic test chart of the catalytic performance of the catalyst in Example 4. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention, but this does not constitute a limitation on the protection scope of the present invention.

[0031] The present invention provides a method for preparing a NiO-CuO / Fe3O4 catalytic material with a three-phase interface, comprising the following steps:

[0032] (1) Take a certain amount of soluble divalent iron salt and dissolve it in 40 ml of ethylene glycol to form solution A;

[0033] (2) Dissolve 0.2 mol of sodium hydroxide in 8 ml of water, then add 30 ml of ethylene glycol and stir to obtain solution B;

[0034] (3) Mixing solution A and solution B and stirring for 1 hour, transferring them into a reactor and reacting them at 130°C for 6 hours, filtering and cleaning, collecting the solid powder sample, and drying them in a vacuum oven at 60°C for 4 hours;

[0035] (4) weighing a certain amount of Fe3O4 powder synthesized in the previous step, placing it in a mixed aqueous solution containing a certain amount of copper acetate and nickel acetate, stirring for 20 minutes, and then placing it in an oven at 60-95°C for 2-3 hours;

[0036] (5) The dried paste can be transferred to a tube furnace and calcined at 450°C for 3 hours under a nitrogen atmosphere.

[0037] The present invention firstly synthesizes Fe3O4 by a solvothermal method, and then deposits NiO-CuO on the surface of Fe3O4 by an impregnation-calcination process, and the obtained sample is a heterogeneous structure with a three-phase interface. The three phase interfaces are NiO-CuO, CuO-Fe3O4, and NiO-Fe3O4, respectively. The charge transfer between the three-phase interfaces can optimize the electronic structure of the catalyst and thus improve its catalytic performance. In addition, the ratio of nickel and copper is effectively controlled during the synthesis process, the entire preparation process is simple to operate, environmentally friendly, and has very good experimental reproducibility, low cost, and is easy to industrialize. The NiO-CuO / Fe3O4 prepared by the method of the present invention has high catalytic activity in the hydrogen production reaction by alcoholysis of ammonia borane, and its TOF value can reach up to 13.5 mol hydrogen min -1 mol Ni+Cu-1 .

[0038] Example 1

[0039] Take 3mmol of FeSO4·7H2O and dissolve it in 40ml of ethylene glycol to form solution A; then dissolve 0.2mol of sodium hydroxide in 8ml of water, then pour in 30ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B for 1 hour, transfer to a reactor and react at 130℃ for 6 hours, filter and wash, collect solid powder samples and place them in a vacuum oven at 60℃ for 4 hours. This sample has no catalytic activity for hydrogen production by alcoholysis of ammonia borane.

[0040] Example 2

[0041] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 1 mmol of copper acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 3.9 mol hydrogen min -1 mol Ni+Cu -1 .

[0042] Example 3

[0043] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.75 mmol of copper acetate and 0.25 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and then transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 6.4 mol hydrogen min - 1 mol Ni+Cu -1 .

[0044] Example 4

[0045] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 13.5 mol hydrogen min - 1 mol Ni+Cu -1 .

[0046] Example 5

[0047] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.25 mmol of copper acetate and 0.75 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and then transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 6.0 mol hydrogen min - 1 mol Ni+Cu -1 .

[0048] Example 6

[0049] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer to a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C for 4 hours. Put 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) into 10 ml of aqueous solution containing 1 mmol of nickel acetate, stir for 20 minutes, place it in an oven at 80°C for 3 hours, and transfer it to a muffle furnace and calcine at 450°C for 3 hours under nitrogen atmosphere. This sample has no catalytic activity for hydrogen production by alcoholysis of ammonia borane.

[0050] Example 7

[0051] Take 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place in an oven at 80°C for 3 hours, and transfer to a muffle furnace for calcination at 450°C for 3 hours under a nitrogen atmosphere. The TOF value of this sample for hydrogen production from alcoholysis of ammonia borane is 4.5 mol hydrogen min -1 mol Ni+Cu -1 .

[0052] Example 8

[0053] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 65°C for 3 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production from alcoholysis of ammonia borane is 7.5 mol hydrogen min - 1 mol Ni+Cu -1 .

[0054] Example 10

[0055] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven at 95°C to dry for 3 hours, and transfer it to a muffle furnace and calcine at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 8.4 mol hydrogen min - 1 mol Ni+Cu -1 .

[0056] Embodiment 11

[0057] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 1.5 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 6.9 mol hydrogen min - 1 mol Ni+Cu -1 .

[0058] Example 12

[0059] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 4.5 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 11.2 mol hydrogen min - 1 mol Ni+Cu -1 .

[0060] Embodiment 13

[0061] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of cobalt acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 1.4 mol hydrogen min - 1 mol Ni+Co -1 .

[0062] Embodiment 14

[0063] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of iron acetate and 0.5 mmol of nickel acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 0.9 mol hydrogen min - 1 mol Ni+Fe -1 .

[0064] Embodiment 15

[0065] Take 3 mmol of FeSO4·7H2O and dissolve it in 40 ml of ethylene glycol to form solution A; then dissolve 0.2 mol of sodium hydroxide in 8 ml of water, and then pour in 30 ml of ethylene glycol and stir to obtain solution B. Mix solution A and solution B and stir for 1 hour, transfer them into a reactor and react at 130°C for 6 hours, filter and wash, collect the solid powder sample and place it in a vacuum oven at 60°C to dry for 4 hours. Place 115.8 mg of Fe3O4 powder synthesized in the previous step (about 0.5 mmol of Fe3O4) in 10 ml of an aqueous solution containing 0.5 mmol of iron acetate and 0.5 mmol of cobalt acetate, stir for 20 minutes, place it in an oven and dry it at 80°C for 3 hours, and then transfer it to a muffle furnace and calcine it at 450°C under a nitrogen atmosphere for 3 hours. The TOF value of this sample for hydrogen production by alcoholysis of ammonia borane is 0.8 mol hydrogen min - 1 mol Fe+Co -1 .

[0066] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface, characterized in that: The following steps are involved: (1) Take a certain amount of soluble divalent iron salt and dissolve it in 40 ml of ethylene glycol to form solution A; (2) Dissolve 0.2 mol of sodium hydroxide in 8 ml of water, then add 30 ml of ethylene glycol and stir to obtain solution B; (3) Mixing solution A and solution B, stirring evenly, transferring them into a reaction kettle, reacting at 130° C. for 6 hours, filtering and cleaning, collecting solid powder samples and placing them in a vacuum oven to dry for a period of time; (4) Weigh a certain amount of Fe3O4 powder synthesized in step (3), place it in a mixed aqueous solution containing a certain amount of copper acetate and nickel acetate, stir for 20 minutes, and then place it in an oven at 60-95°C to dry for 2-3 hours; (5) After drying into a paste, the paste was transferred to a tube furnace and calcined at 450° C. for 3 hours in a nitrogen atmosphere.

2. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 1, characterized in that: The soluble divalent iron salt in step (1) is FeSO4·7H2O.

3. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 1, characterized in that: In step (4), the mixture is placed in 10 ml of an aqueous solution containing 0.5 mmol of copper acetate and 0.5 mmol of nickel acetate.

4. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 1, characterized in that: The stirring time in step (3) is 1 hour.

5. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 3, characterized in that: After stirring for 20 minutes in step (4), the mixture was placed in an oven and dried at 80° C. for 3 hours.

6. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 1, characterized in that: Step (1) 3 mmol of FeSO4·7H2O was dissolved in 40 ml of ethylene glycol to form solution A.

7. The method for preparing a NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 1, characterized in that: In step (3), the solid powder sample is dried in a vacuum oven at 60° C. for 4 hours.

8. A NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface, characterized in that: Prepared according to any one of claims 1 to 7.

9. The NiO-CuO / Fe3O4 ammonia borane alcoholysis hydrogen production catalyst having a three-phase interface as claimed in claim 8, characterized in that: The catalyst has weak ferromagnetism.

10. Use of the ammonia borane alcoholysis hydrogen production catalyst prepared by the method according to any one of claims 1 to 7 in catalyzing the alcoholysis of ammonia borane to produce hydrogen.